Evidence that the TRPV1 S1-S4 membrane domain contributes to thermosensing - Minjoo Kim (Nature Portfolio, 2020)
The TRPV1 ion channel is a heat-sensing receptor that is also activated by vanilloid compounds, but the molecular underpinnings of thermosensing have remained elusive. Here authors use in solution NMR on the isolated human TRPV1 S1-S4 domain and show that this domain undergoes a non-denaturing temperature-dependent transition with a high thermosensitivity.